Spatial environmental risk evaluation of potential toxic elements in stream sediments - Antunes, Isabel Margarida Horta Ribeiro (2018)
Potential toxic elements (PTE), in stream sediments, were used as contamination indicators for the definition of high-/low-grade spatial clusters in the Monfortinho area (Central Portugal). A set of 271 stream sediment samples was used for spatial modelling and further definition of rings of enrichment-high and low rings. A three-step multivariate statistical and geostatistical approach was used: (1) principal components analysis for PTE's association evaluation and dimensionality reduction; (2) ordinary kriging as an unbiased interpolator for content inference and construction of a continuous representation of the considered attributes, at any arbitrary spatial location; (3) G clustering algorithm for the definition of high and low significance clusters. A moderate contamination in stream sediments is observed for almost all the considered PTE and a very high contamination for Ba, Cr and B. High contamination clusters are observed for Fe, Ni, Ba, Cu, B, Zn, V-northwest and southeast clusters-and for Cr-north and southwest clusters. The contamination degree index varies from moderate to high, which is mainly associated with the old mineralizations. The high computed rings often overlap the areas of abandoned Ba-Zn mineralization, as well as the sedimentary gold concentrations, along the Erges River banks. Tin and Cd spatial distribution may be related to former cassiterite exploitations in the survey area. Chromium is possibly connected with the schists. The definition of clusters with a PTE spatial enrichment will allow for the identification of contamination activities and therefore, the definition of adequate monitoring and mitigation actions.